Delta Opioid Peptides Derived from Plant Proteins - Yoshikawa, M.; Takahashi, M.; Yang, S. (Current Pharmaceutical Design, 2003)
Opioid peptides showing selectivity for d receptor have been isolated from enzymatic digests of plant proteins. Five peptides were derived from wheat gluten, and named gluten exorphins A5, A4, B5, B4 and C. Two opioid peptides were also released from spinach ribulosebisphosphate- carboxylase / oxygenase (Rubisco), and named rubiscolins-5 and -6. Among them, gluten exorphin 5A (Gly-Tyr-Tyr-Pro-Thr) and rubiscolin-6 (Tyr-Pro-Leu-Asp-Leu-Phe) improved learning performance in step-through type passive avoidance test after post-training oral administration in mice at doses of 300 mg / kg and 100 mg / kg, respectively, which are smaller than those required for antinociceptive activity.
Keywords: anxiolytic